Improving farmers’ welfare through gastrointestinal nematode control in cattle at Aman Sentosa BUMDes for food security - Zulfikar Zulfikar; Abdul Malik; Al Mahfud Saputra; Muhammad Rizal (LPPM Universitas Syiah Kuala, 2026)
Background and Aim: Gastrointestinal nematode (GIN) infections in cattle remain a major challenge affecting livestock productivity and farmers’ welfare in rural communities. This community service program was conducted at BUMDES Aman Sentosa, Darul Aman Village, South Peusangan Subdistrict, Bireuen Regency, Aceh Province, aiming to improve farmers’ welfare through GIN control in cattle and the implementation of sustainable and healthy livestock management practices. Methods: The program applied participatory and educational approaches through extension activities, training sessions, and field practices involving local cattle farmers. The activities included education on livestock disease prevention, proper stall management, production of alternative feed from local raw materials, and community-based livestock marketing strategies. Results: The program resulted in a 30–35% increase in farmers’ knowledge regarding livestock health and management, a 40% reduction in cattle disease cases associated with parasitic infections, and improved cattle sales through the adoption of modernized marketing systems. Conclusion: The implementation of integrated livestock health management and farmer education significantly contributed to improving cattle productivity, strengthening farmers’ economic independence, and enhancing the role of BUMDES Aman Sentosa as a sustainable community-based livestock and rural economic empowerment center.